2014
DOI: 10.3748/wjg.v20.i36.13060
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium aviumsubspeciesparatuberculosisin the etiology of Crohn’s disease, cause or epiphenomenon?

Abstract: The origin of inflammatory bowel disease is unknown. Attempts have been made to isolate a microorganism that could explain the onset of inflammation, but no pathological agent has ever been identified. Johne's disease is a granulomatous chronic enteritis of cattle and sheep caused by Mycobacterium avium subspecies paratuberculosis (MAP) and shows some analogies with Crohn's disease (CD). Several studies have tried to clarify if MAP has a role in the etiology of CD. The present article provides an overview of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 79 publications
1
26
0
2
Order By: Relevance
“…Mycobacterium avium subsp. paratuberculosis has also been investigated as a potential cause of Crohn's disease owing to its ability to cause chronic granulomatous enteritis in sheep and cattle 4144 ; however, clinical studies have not borne out this hypothesis 45,46 . Similarly, a specific association between Fusobacterium nucleatum , ulcerative colitis and the development of colorectal cancer has been proposed based on the isolation of a highly invasive strain from patients with ulcerative colitis, but a clear cause-and-effect relationship has not been proven 47,48 .…”
Section: Microbiota Composition and Ibdmentioning
confidence: 99%
“…Mycobacterium avium subsp. paratuberculosis has also been investigated as a potential cause of Crohn's disease owing to its ability to cause chronic granulomatous enteritis in sheep and cattle 4144 ; however, clinical studies have not borne out this hypothesis 45,46 . Similarly, a specific association between Fusobacterium nucleatum , ulcerative colitis and the development of colorectal cancer has been proposed based on the isolation of a highly invasive strain from patients with ulcerative colitis, but a clear cause-and-effect relationship has not been proven 47,48 .…”
Section: Microbiota Composition and Ibdmentioning
confidence: 99%
“…Studies have shown however, that it is extremely difficult to grow MAP from human samples where MAP exists with a modified cell wall making it resistant to standard identity staining techniques (Sechi et al, 2005) couple with specific growth requirements such as certain levels of iron which it sources from its hosts . Additionally, JD does not display some of the manifestations of CD such as the segmental localization and features such as fistula, fissures, bleeding, stenosis, adhesions, perforation and the formation of abscesses (Liverani et al, 2014). In order to prove without a doubt that MAP causes IBD, live organisms must be isolated and cultured from a patient and shown to be able to infect and cause morbidity in a second host.…”
Section: Map and Human Morbiditymentioning
confidence: 99%
“…In 1913, Dalziel reported the link between MAP and human Morbus Crohn disease (CD). Several studies have demonstrated the presence of MAP in CD cases, but the causative role of MAP in CD is not established yet [11, 12]. Similarly McNees and colleagues reported that MAP can be cultured from mononuclear cells of Crohn’s disease patient’s but it does not establish the etiology [13].…”
Section: Introductionmentioning
confidence: 99%